A Historiography of Traditional Medicine in East Africa - BEZABIH MAIL, ADANE KASSIE (Innovare Journal of Social Sciences, 2014)
Abstract Traditional medicine has been used by the peoples of Eastern Africa since time immemorial. This paper, therefore, tries to assess the various works which were so far written on the subject. A number of scholars wrote on the nature, essence, type and social and health effects of traditional medicine in the region. In fact, most scholars argued that the use of traditional medicine gradually decreases following the expansion of cosmopolitan medicine in the region. Pre-colonial East Africa was known in massive use of traditional medicine. However, the advent of colonialism in the region and the expansion of modern clinics and hospitals to provide health service to the society have seriously affected the hegemony of traditional medicine in the region. Though much remains to be done, the available literature on the subject attests that the role of traditional medicine on the peoples of the region is still immense. Moreover, regardless of their methodological problems and narrow scope, the literature has the power to inspire practicing scholars to work more on the subject.